Investigating the Impact of Digital Literacy Instruction in Virtual School towards English Learning Program - Astuti, Nurul Ismi; Khaerati Syam, Ummi; Sastrawati, Ika (Journal of Computer Interaction in Education, 2020)
This research was to find out the impact of google forms that were used by the teacher as an assessment tool at SMK Persada Tamalatea. This research used a descriptive qualitative method. The instrument was employed through observation and interview to know the impact that the teacher felt using google form as an instructional technology tool in assessing students’ knowledge during distance learning at SMK Persada Tamalatea.Based on the results obtained, the results of this research indicate that the use of google forms has more positive than negative impacts on teachers in performing assessments during the pandemic situation. It can be concluded that the positive impacts are in terms of ease of use, efficiency in time, energy and cost, attractive appearance, helpful features, accuracy in scoring, minimized paper usage, and making the teacher more technologically literate. It is quite effective to develop it as an assessment tool in the learning process, especially in online learning. Nevertheless, it required a stable connection and google account. It is incapable of detecting fraud, requires additional security, and it cannot be adapted to the bold, italic and underlined word functionalities. However, teachers have their own ways of solving the problem.